Long-term survival of patients with cerebrovascular accident, depending on sex and age: data from the REGION-M registry - S. N. Tolpygina; A. V. Zagrebelny; M. I. Chernysheva; N. P. Kutishenko; V. P. Voronina; N. A. Dmitrieva; O. V. Lerman; Yu. V. Lukina; M. M. Lukyanov; E. Yu. Okshina; N. E. Parsadanyan; S. Yu. Martsevich; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To study the long-term survival of patients with cerebrovascular accident, depending on sex and age.Material and methods. The outpatient part of the REGION-M registry (patients with cerebrovascular accident, hospitalized in a Moscow hospital) included 684 patients assigned to the City Polyclinic № 64 (Moscow), discharged from the F. I. Inozemtsev City Clinical Hospital (Moscow) in the period from January 1, 2012 to April 30, 2017 with a diagnosis of stroke, which were divided into 5 age groups: group 1 — ≤50 years, n=72 (10,5%), group 2 — 51-60 years old, n=122 (17,8%), group 3 — 61-70 years old, n=156 (22,8%), group 4 — 71-80 years old, n=185 (27,0%) and group 5 — ≥81 years old, n=149 (21,8%). The survival of patients was assessed at the 2nd and 3rd stages after 4,2 (2,4-5,6) and 5,5 (2,4-7,0) years.Results. The mortality of patients in the long-term follow-up period significantly increased with age. There were following mortality rate for stages 2 and 3 stages: 18-50 years old — 8,3 and 22,2%, 51-60 years old — 18 and 36,9%, 61-70 years old — 41 and 56,4%, 71-80 years old — 54,1 and 73%, >81 years — 76,5 and 87,9% (p<0,0001 for all groups). At stages 2 and 3, mortality among men was higher than among women in groups 2-4, below in group 1 and did not differ in the oldest age group. In multivariate analysis, the following factors had prognostic significance: age — hazard ratio (HR) of death, 1,035 (95% confidence interval (CI): 1,029-1,041, p=0,001), sex — HR, 0,720 (95% CI: 0,43-0,123, p=0,001) and disability before stroke — HR, 0,999 (95% CI: 0,998-1,000, p=0,002).Conclusion. In long-term follow-up, the mortality of patients with cerebrovascular accident was significantly higher in older age groups, as well as among men.